PBPK‐led assessment of antimalarial drugs as candidates for Covid‐19: Simulating concentrations at the site of action to inform repurposing strategies - Nada Abla; Lisa M. Almond; Jennifer J. Bonner; Naomi Richardson; Timothy N. C. Wells; Jörg J. Möhrle (Wiley, 2024)
Abstract The urgent need for safe, efficacious, and accessible drug treatments to treat coronavirus disease 2019 (COVID‐19) prompted a global effort to evaluate drug repurposing opportunities. Pyronaridine and amodiaquine are both components of approved antimalarials with in vitro activity against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). In vitro activity does not always translate to clinical efficacy across a therapeutic dose range. This study applied available, verified, physiologically based pharmacokinetic (PBPK) models for pyronaridine, amodiaquine, and its active metabolite N‐desethylamodiaquine (DEAQ) to predict drug concentrations in lung tissue relative to plasma or blood in the default healthy virtual population. Lung exposures were compared to published data across the reported range of in vitro EC50 values against SARS‐CoV‐2. In the multicompartment permeability‐limited PBPK model, the predicted total Cmax in lung mass for pyronaridine was 34.2 μM on Day 3, 30.5‐fold greater than in blood (1.12 μM) and for amodiaquine was 0.530 μM, 8.83‐fold greater than in plasma (0.060 μM). In the perfusion‐limited PBPK model, the DEAQ predicted total Cmax on Day 3 in lung mass (30.2 μM) was 21.4‐fold greater than for plasma (1.41 μM). Based on the available in vitro data, predicted drug concentrations in lung tissue for pyronaridine and DEAQ, but not amodiaquine, appeared sufficient to inhibit SARS‐CoV‐2 replication. Simulations indicated standard dosing regimens of pyronaridine‐artesunate and artesunate‐amodiaquine have potential to treat COVID‐19. These findings informed repurposing strategies to select the most relevant compounds for clinical investigation in COVID‐19. Clinical data for model verification may become available from ongoing clinical studies.